Plastic additives in commercial fish of Aegean and Ionian Seas and potential hazard to human health - Marmara, Dimitra; Brundo, Maria Violetta; Pecoraro, Roberta; Scalisi, Elena Maria; Contino, Martina; Sica, Carmen; Ferruggia, Greta; Indelicato, Stefania; Velardita, Rosario; Tiralongo, Francesco; Krasakopoulou, Evangelia (Frontiers in Marine Science, 2024)
Plastic additives include a wide range of pollutants, added throughout the production process of plastics aiming to improve their properties. Given that they are not chemically bound to the plastic items, they can easily mitigrate in the marine environment allowing their uptake and accumulation in marine organisms. Representatives of phthalates (PAEs) and bisphenols have been characterized for their ability to impact marine organisms, but also humans via fish and seafood consumption. In this study, the concentrations of PAEs and Bisphenol A (BPA) were determined in the muscle and the gastrointestinal tract (GIT) of E.encrasicolus, S.pilchardus, B.boops, and M.barbatus from two important divisions of fisheries (North Aegean and the Ionian Seas, thereof NAS and IOS respectively) of the Mediterranean Sea. The level of contamination varied among the different species and geographical locations. DEHP (bis(2-ethylhexyl) phthalate) had the highest mean concentrations of the examined PAEs for all four species. Statistically significant differences of DEHP mean concentrations were observed between the tissues of B.boops (NAS) and S.pilchardus (IOS) (p < 0.05, Wilcoxon rank test). DIDP (diisodecylphthalate) was the following mostly found PAEs, although no statistically significant differences were presented between sites, species and tissues. DINP (di-isononylphthalate) was recorded only in the GIT of E.encrasicolus (NAS), while the rest of the examined PAEs was present in a part smaller subset of the samples. Noticeable, the parent diester DBP and the metabolic monoester MNBP were concurrently detected in a part of the analyzed samples. The level of risk via fish consumption, based on the Estimated Daily Intake and the Target Hazard Quotient (THQ), showed that for PAEs had a low likelihood of negative effect to occur for every scenario that was examined. Contrary, THQ for BPA indicated there was a high likelihood of adverse effect to be presented in children and adults for both areas.